1989
DOI: 10.1590/s0036-46651989000600010
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal and pulmonary entomophthoromycosis with superior vena cava syndrome: case report

Abstract: SUMMARYThe firs t cas e o f mediastina l an d pulmonar y entomophthoromycosi s wit h sup e rior ven a cava syndrom e i s reported. Th e patien t presente d wit h a history o f edem a of th e face , nec k an d uppe r limb s a s wel l a s collatera l circulatio n i n th e anterio r

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…7 are comparable to the zygospores developed by C. incongruus in culture. Similarly, Coelho-Filho (178) and Marwaha et al (179) also reported systemic cases caused by putative Conidiobolus species involving the superior vena cava without culture. However, entomophthoralean fungi rarely invade blood vessels, and the pathological features of the observed slender hyphae are not typical of these fungi, so the possibility of infection caused by P. insidiosum has to be taken into consideration (114).…”
Section: Clinical Features Of Entomophthoramycosis Conidiobolomycosismentioning
confidence: 93%
“…7 are comparable to the zygospores developed by C. incongruus in culture. Similarly, Coelho-Filho (178) and Marwaha et al (179) also reported systemic cases caused by putative Conidiobolus species involving the superior vena cava without culture. However, entomophthoralean fungi rarely invade blood vessels, and the pathological features of the observed slender hyphae are not typical of these fungi, so the possibility of infection caused by P. insidiosum has to be taken into consideration (114).…”
Section: Clinical Features Of Entomophthoramycosis Conidiobolomycosismentioning
confidence: 93%